Terminological debate over language impairment in children: forward movement and sticking points. - Reilly, S; Bishop, D; Tomblin, B (Wiley-Blackwell Publishing Ltd, 2014)
BACKGROUND: There is no agreed terminology for describing childhood language problems. In this special issue Reilly et al. and Bishop review the history of the most widely used label, 'specific language impairment' (SLI), and discuss the pros and cons of various terms. Commentators from a range of backgrounds, in terms of both discipline and geographical background, were then invited to respond to each lead article. AIMS: To summarize the main points made by the commentators and identify (1) points of consensus and disagreement, (2) issues for debate including the drivers for change and diagnostic criteria, and (3) the way forward. CONCLUSIONS and IMPLICATIONS: There was some common ground, namely that the current situation is not tenable because it impedes clinical and research progress and impacts on access to services. There were also wide-ranging disagreements about which term should be adopted. However, before debating the broad diagnostic label it is essential to consider the diagnostic criteria and the systems used to classify childhood language problems. This is critical in order to facilitate communication between and among clinicians and researchers, across sectors (in particular health and education), with the media and policy-makers and with families and individuals who have language problems. We suggest four criteria be taken into account when establishing diagnostic criteria, including: (1) the features of language, (2) the impact on functioning and participation, (3) the presence/absence of other impairments, and (4) the language trajectory or pathway and age of onset. In future, these criteria may expand to include the genetic and neural markers for language problems. Finally, there was overarching agreement about the need for an international and multidisciplinary forum to move this debate forward. The purpose would be to develop consensus regarding the diagnostic criteria and diagnostic label for children with language problems. This process should include canvassing the views of families and people with language problems as well as the views of policy-makers.